A critical review of roadway sustainable rating systems. (December 2020) - Mattinzioli, T.; Sol-Sánchez, M.; Martínez, G.; Rubio-Gámez, M.
Highlights: Seven sustainable roadway rating systems were critically reviewed. Roads can be assessed with infrastructure, roadway or pavement rating systems. Rating systems mainly focus on resource and energy use. Third-party rating systems adhere more to the three-pillars of sustainability. Rating systems could greatly assist in social sustainability quantification. Abstract: Multiple rating systems have been established to enhance the sustainable design and management of roadway projects. These systems are based on current best practices and demonstrate significant potential for assisting project managers in achieving environmentally sustainable and socially resilient smart transportation assets. HFowever, as it stands there is a significant lack of understanding on these systems, and thus lack of confidence in their implementation. Thus, this study aims to develop an up-to-date critical review on the most prominent rating systems currently in the global market. Specifically, the CEEQUAL, Envision, BE 2 ST-in-Highways, Greenroads, GreenLITES, Invest and GreenPave systems were selected and analysed in terms of their scopes, structures, common criteria, three-pillar adherence, and asset management effectiveness. The results of this study found: 1) system characteristics can be categorised by system scope (infrastructure, roadway or pavement) and assessment type (self-assessment or third-party, 2) third-party systems assessed the three-pillars of sustainability and the identified macro-categories more homogeneously, and 3) rating systems show strong potential for the social assessment of projects, but their consideration of life-cycle assessment could be more outcome-orientated. Future work should apply the rating systems to project case studies to further identify implementation, contextual and indicator pluralism issues.